Introducing “Cap Concept” in a Class Room Learning for the Students to Achieve Success - Gururaj Ganapati Gouda; Laveena D’Mello, (International Journal of Management, Technology and Social Sciences (IJMTS), 2019)
Unchanged Indian education system has blocked student’s interest in active learning in the classroom. All the time and all the ways students are demotivated, distracted and pressurized. Today class room teaching made the teachers get limited for completion of the portion and also the modern educational institutions are wordless in beyond classroom teaching. Corporal punishments, exams and home works are only become the deferent parameters to measure the children. It made all the way children feel helpless, hopeless and worthless. In the classroom students are only expected by the teachers to be silent and pay attention towards continues sessions. The other hand teachers have no way to pay little time to make children get motivated and active. However unless we create a positive and motivational teaching in the classroom no use whatever we inculcate, only we can complete the portion not inculcating values of concept we teach. The main objective of this study is to implement the cap concept, which creates student’s attention towards positive change in their attitude and behaviour, concentration in the class, improved confidence level, encouraged towards social involvement and many more. Cap concept is nothing but awarding an attractive cap to a student in the classroom for the recognition of a little positive work that he or she has done. The student awarded cap will wear it and sit in the particular session. It influences the student to feel proud by the identity and claps given by the classmates. The particular student will also will start liking and accepting the particular teacher and their guidance. The study made it very clear that the cap concept will surely help the teacher to encourage the students with several behavioural problems and bring positive change in their day todays leaving. As per the data 64% of respondents have expressed positive improvement in their behaviour. The activity is conducted for 50 high school students; 25 girls and 25 boys. Interview schedule, primary and secondary methods are used and the study is descriptive in nature.